Mutagenicity of Chinese traditional medicine Semen Armeniacae amarum by two modified Ames tests - Cai Yupin; Tian Xiao; Zhang Hui; Liu Bo; Jin Jianling; Gao Peiji (BMC, 2009)
Abstract Background Semen armeniacae amarum (SAA) is a Chinese traditional medicine and has long been used to control acute lower respiratory tract infection and asthma, as a result of its expectorant and antiasthmatic activities. However, its mutagenicity in vitro and in vivo has not yet been reported. The Ames test for mutagenicity is used worldwide. The histidine contained in biological samples can induce histidine-deficient cells to replicate, which results in more his+ colonies than in negative control cells, therefore false-positive results may be obtained. So, it becomes a prerequisite to exclude the effects of any residual histidine from samples when they are assayed for their mutagenicity. Chinese traditional herbs, such as SAA, are histidine-containing biological sample, need modified Ames tests to assay their in vitro mutagenicity. Methods The mutagenicity of SAA was evaluated by the standard and two modified Ames tests. The first modification used the plate incorporation test same as standard Ames teat, but with new negative control systems, in which different amounts of histidine corresponding to different concentrations of SAA was incorporated. When the number of his+ revertants in SAA experiments was compared with that in new negative control, the effect of histidine contained in SAA could be eliminated. The second modification used a liquid suspension test similar to the standard Ames test, except with histidine-rich instead of histidine-limited medium. The aim of this change was to conceal the effect of histidine contained in SAA on the final counting of his+ revertants, and therefore to exclude false-positive results of SAA in the Ames test. Furthermore, the effect of SAA on chromosomal aberration in mammalian bone marrow cells was tested. Results The standard Ames test showed a positive result for mutagenicity of SAA. In contrast, a negative response was obtained with the modified plate incorporation and modified suspension Ames tests. Moreover, no apparent chromosomal aberrations were observed in mammalian bone marrow cells treated with SAA. Conclusion The standard Ames test was not suitable for evaluating the mutagenicity of SAA, because false-positive result could be resulted by the histidine content in SAA. However, the two modified Ames tests were suitable, because the experimental results proved that the effect of histidine in SAA and therefore the false-positive result were effectively excluded in these two modified Ames tests. This conclusion needs more experimental data to support in the future. Moreover, the experimental results illustrated that SAA had no mutagenicity in vitro and in vivo. This was in agreement with the clinical safety of SAA long-term used in China.